Market Driven Pedagogy For Financial Economics Decisions – An Exploratory Study - Lim, Kim Her (2013)
The exploratory study attempted to expand existing partial resolutions of graduates’ employability with the market driven pedagogy of financial economics decision (FED) program. The study related the effectiveness of the market driven pedagogy of FED to the motivational aspects of learning on a purposive sample. The methodology used the Repeated Measure design with a series of analysis of data mining approach onto an empirical data created by the existing research instrument. The analyses used were Delphi, Paired t-Test, one-way Repeated Measures ANOVA and Bayesian transformation procedure to determine a pedagogy index (PI). PI considered only the Affective and Cognitive motivation variables for learning. The Conative and Social motivation variables were also analyzed to provide secondary support for discussion and further reasoning. The exploratory study supported Kline’s (2004) argument list of fallacies in null hypothesis. Issues formulating the problem statement and significant findings about motivation for learning also concurred with recent independent studies. Additionally, the study informed that concept mapping and decision tree were within the top 20% cognitive skills desired by interns. Social learning through continuous professional development and advent of computing technology was seen as keen media for learning. Though both genders learned different and were extrinsic motivated; their professional abilities were acceptable by industries. The implicative conclusion of the study was that suitable instructional pedagogy had increased motivation for learning FED. Incremental learning of FED was expected from facilitation by computer based instructional pedagogy towards social learning. At the same time, educational technology catalyst now available for Science, Technology, Engineering and Mathematics known as Pedagogy 3.0 was expected to extend to FED.